Citizen Kane [videorecording (Blu-Ray)] - Welles, Orson, 1915-1985; Cotten, Joseph, 1905-1994; Comingore, Dorothy, 1913-1971; Sloane, Everett, 1909-1965 (Warner Bros. Entertainment, 2016)
The story of an immensely weathly newspaper publisher, as he is remembered by his friends and former wife after his death.